2015
DOI: 10.1177/1066896915617828
|View full text |Cite
|
Sign up to set email alerts
|

FGF23-Associated Tumor-Induced Osteomalacia in a Patient With Small Cell Carcinoma

Abstract: Tumor-induced osteomalacia (TIO) is typically caused by phosphaturic mesenchymal tumor (PMT) that secretes the phosphaturic hormone, fibroblast growth factor-23 (FGF23), resulting in decreased phosphate reabsorption in kidneys, hypophosphatemia, and finally osteomalacia. Rare cases of malignant tumor manifesting with TIO other than PMT had been reported, although in most of these reports, except one, circulating FGF23 levels were not evaluated and tissue expressing of FGF23 was not confirmed. In this article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth underlining that while Fetuin-A showed a higher expression in primary hepatocytes compared to HepG2; no difference was evident for FGF23 expression between the two diverse types of cells. The lack of any difference between the primary hepatocytes and the HepG2 cells is an important finding, since it is known that tumoral liver cells can non-physiologically express many FGFs (FGF8, FGF17, FGF18) 36 , 37 . In any case, our results are confirmatory of previous studies, which have demonstrated that FGF23 is expressed also in the liver cells 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Distant lung metastasis has also been reported to be witnessed with a histologically benign PMT [ 53 , 54 ]. PMTs can present as paraneoplastic syndrome of carcinoma as well, relative reports involving ovarian cancer [ 55 ], prostate cancer [ 56 ], colon cancer [ 57 ] and lung cancer [ 58 ].…”
Section: Clinical Description and Evaluationmentioning
confidence: 99%